1998
DOI: 10.1097/00003072-199808000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Retention of Tc-99m MIBI in Mediastinal Lymphomas As a Predictor of Chemotherapeutic Response Demonstrated by Consecutive Thoracic SPECT Imaging

Abstract: Tc-99m MIBI is used as a tumor imaging agent and has been proposed to measure p-glycoprotein function, which plays an important role in tumor multidrug resistance to chemotherapy. It has been reported that lung cancer and breast cancer with a high retention of Tc-99m MIBI have been more responsive to chemotherapy than tumors with low retention. Thus Tc-99m MIBI SPECT could be used as a measure of p glycoprotein function and consequently may serve as a predictor of the tumor's responsiveness to chemotherapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Previous reports concerning pre-therapeutic scintigraphic prediction of tumour response to treatment have suggested that poor responders will exhibit less intense accumulation of 99m Tc-MIBI than good responders [8,9,10,11,12,13,14,15,16]. Given these observations, we hypothesized that hypoxic conditions would interfere with the accumulation of 99m Tc-MIBI in tumour cells.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous reports concerning pre-therapeutic scintigraphic prediction of tumour response to treatment have suggested that poor responders will exhibit less intense accumulation of 99m Tc-MIBI than good responders [8,9,10,11,12,13,14,15,16]. Given these observations, we hypothesized that hypoxic conditions would interfere with the accumulation of 99m Tc-MIBI in tumour cells.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, 99m Tc-MIBI has been used to monitor lesion response during and at the conclusion of treatments such as radiotherapy and chemotherapy [5,6,7,8]: lesions showing a favourable response demonstrated a reduction of tracer accumulation due to the treatment. More interestingly, 99m Tc-MIBI scintigraphy may enable pre-therapeutic prediction of treatment outcomes [8,9,10,11,12,13,14,15,16]. A number of studies have been conducted regarding small cell and non-small cell lung cancer [8,9,10,11,12,13,14], malignant lymphoma [15] and breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…99m Tc-Sestamibi scan represents P-gp expression more accurately than other prognostic factors and is able to predict the chemotherapy response in malignant lymphomas [14,[78][79][80][81][82]. In fact, 99m…”
Section: Lymphomas and Multiple Myelomamentioning
confidence: 99%
“…[38][39][40] Of this list of radiolabeled drugs, only 11 C-daunorubicin and 11 C-verapamil have been used to any significant extent. [54][55][56][57][58][59] Sestamibi is now being used to monitor the effectiveness of Pgp modulator regimens. 41 Increased levels of tracer in the brain were noted in mice treated with cyclosporin A and in mice in which the mdr1 gene had been knocked out.…”
Section: Functional Imaging Of Multidrug Resistancementioning
confidence: 99%